O zabiegach edytorskich w książkach wspierających rozwój językowy małych czytelników - Ostasz, Maria; Pustuła, Marta (Dydaktyka Polonistyczna, 2019)
Children’s book editing is an interdisciplinary field of research combining typography, pedagogy and didactics. The article deals with distinctions which are important, but still it is a little recognized and reviewed issue in the field of editorial means, which should be in a properly designed book subordinated to the basic functions: organization, navigation and cohesion. The examples presented showed that each element used in a children’s book design should serve at least one of these functions, as their effect is extended to support the learning of reading, articulation, spelling practice, etc. Typographical errors in the use of distinctions, causing reading to be disturbed, have also been highlighted. The aesthetics of such a book may have a positive or negative impact on the hygiene of reading - it may make it difficult to learn to read or even discourage one from dealing with a book. Properly applied - matched typographic distinctions improve the legibility of the text, i.e. make it easier for children - not skilled enough readers – to get used to the text and its educational layer. Aesthetics and high quality of publications aimed at children is a broad and still not very well described area of research, and this article is an attempt to raise awareness of this issue.